Comparing space adaptability of diamond-like carbon and molybdenum disulfide films toward synergistic lubrication. (August 2018) - Zhuang, Wenhua; Fan, Xiaoqiang; Li, Wen; Li, Hao; Zhang, Lin; Peng, Jinfang; Cai, Zhenbing; Mo, Jiliang; Zhang, Guangan; Zhu, Minhao
Abstract: Space irradiation-induced damage to onefold lubricants including four multialkylated cyclopentanes (MACs) space greases, Chromium doped diamond-like carbon (Cr-DLC) and molybdenum disulfide (MoS2 ) films was first investigated under simulated space environment (atomic oxygen (AO) and proton (PR)). Then solid-grease synergistic lubrication systems were prepared via spinning four space greases on Cr-DLC and MoS2 film, and their tribological behaviors were evaluated under simulated space environment including ultra-vacuum, AO and PR irradiation, low temperature (−100 °C). The irradiated damage mechanism and friction mechanism were explored by surface/interface analysis techniques. The results demonstrates that Cr-DLC film have better space adaptability than MoS2 film because irradiation induced partial transition of Cr-DLC's micro-structure with the decrease in I D /I G ratio from 1.50 to 1.26 and the increase of sp 3 content from 0.24 to 0.59, while the surface morphology and micro-structure of MoS2 film have dramatically changed. Solid-grease synergistic lubrication systems provide excellent friction-reducing and anti-wear behaviors (friction coefficient can be reduced up to below 0.05 under the special working conditions). Such excellent tribological performance of Cr-DLC-grease lubrication coatings is attributed to the friction-induced graphitization at the sliding interface, while that of MoS2 film mainly depends on its original structure/merits under greases lubrication. Graphical abstract: Image